An orientation for coastal disaster risks management and prevention policy in a global warming context: Case study in Ouvea (New Caledonia). (July 2020) - Le Duff, Matthieu; Dumas, Pascal; Allenbach, Michel; Cohen, Olivier
Abstract: The impact of global warming on coastal areas, in terms of erosion, flooding and environmental change is a source of concerns for many peoples in the Pacific region. In New Caledonia, Ouvea atoll is one of the most vulnerable areas to sea level rise. The population strongly oriented towards his lagoon, is concerned about shoreline erosion and wants to build a climate change adaptation strategy. This paper presents a research-action device aimed to renforce people's resilience in the proper regulatory environment to customary Kanak lands. The creation of a coastline participatory monitoring as data acquisition instrument, and sharing "inhabitants" and "experts" knowledges, is the heart of the approach. The dissemination of information to the population is one of the aims.